Effects of modified constraint-induced movement therapy in the recovery of upper extremity function affected by a stroke: a single-blind randomized parallel trial-comparing group versus individual intervention. Issue 1 (March 2018) - Doussoulin, Arlette; Rivas, Claudia; Rivas, Rodrigo; Saiz, José
Abstract : An extensive corpus of literature supports the positive impact of constraint-induced movement therapy (CIMT) on neuroplasticity and the recovery of function. However, its clinical applicability is limited by the time of intervention and individual modality. We propose to assess the efficacy of modified CIMT protocols through a group therapy intervention. To determine the effectiveness of a group therapy, compared with individual modified CIMT, in increasing the use and functionality of movement of a paretic upper limb. The study was a single-blind, randomized parallel trial. Thirty-six patients who had had a stroke more than 6 months previously were divided randomly into two intervention groups. The independent variable was the implementation of group or individual modalities for 3 h for 10 consecutive days and the dependent variables were evaluated by the Motor Activity Log and Action Research Arm Test, at baseline (preintervention evaluation), end (postintervention evaluation), and 6 months after intervention (follow-up). By controlling the preintervention evaluations, analyses of covariance indicated that both dependent variables presented significant differences in favor of the group therapy at both the postintervention evaluation and the follow-up evaluations. Both types of intervention generated increases in the function and use of the upper extremity, with these increases being higher in the group therapy. The effects of the group therapy modality were maintained 6 months after the intervention ended.